A comprehensive investigation on the chemical structure character of spinnable pitch for improving and optimizing the oxidative stabilization of coal tar pitch-based fiber. (14th May 2021) - Niu, Hao; Zuo, Pingping; Shen, Wenzhong; Qu, Shijie
Abstract: Oxidative stabilization is the critical step to maintain the fibrous morphology of pitch fiber and affects mechanical properties of resultant carbon fiber, but the detailed oxidation mechanism is still unclear because of the complex polycyclic aromatic hydrocarbons composition in pitch fiber. In here, pitch fiber was obtained from coal tar pitch followed by air-blowing and spinning. The chemical structure character of corresponding fibers before and after oxidative stabilization at different temperatures (260–320 °C) and durations (2–12 h) were analyzed. The results indicated that aromatic nucleus in spinnable pitch was gradually increased, while aliphatic chains were gradually shorten with prolongation of air-blowing time. The spinnable pitch obtained by air-blowing at 330 °C for 4 h showed excellent spinning performance, and the as-spun pitch fiber displayed a higher oxidative stabilization efficiency because the lower oxygen content was introduced and more C-O-C groups were formed in the resultant oxidative stabilized pitch fiber. The obtained pitch-based carbon fiber, after carbonizing at 1000 °C, showed excellent mechanical properties with tensile strength of 1068.7 ± 100.0 MPa and Young's modulus of 52.5 ± 9.8 GPa. This work provided a facile approach to improve and optimize the oxidative stabilization efficiency for pitch carbon fiber preparation. Graphical abstract: The aromatic nucleus increased and aliphatic chains decreased in spinnable pitch with air-blowing. The spinnable pitch obtained by air-blowing at 330 °C for 4 h showed excellent spinning performance, facile oxidative stabilization, high tensile strength and Young's modulus. Image 1 Highlights: The aromatic nucleus increased and aliphatic chains decreased in spinnable pitch with air-blowing. ISP4 exhibited excellent spinnability and oxidative stabilization efficiency due to due to its larger aromatic nucleus and higher average molecular weight. The C-O-C in stabilized pitch fiber was beneficial to the mecanical properties of resultant carbon fiber.